BRIDGING GAPS IN FINTECH ADOPTION: A MULTI-THEORETICAL REVIEW AND INTEGRATED FRAMEWORK FOR EMERGING ECONOMIES - Islam, Md Kamrul; Tamzid, Mohammad; Hussain, Mohammad Delwar (Veredas do Direito, 2025)
Recent advances in financial technology (FinTech) impact not only the global financial services industry but also the integration of financial services in economically emerging countries. However, uneven integration of FinTech in emerging economies is still due to various technological, social, and institutional gaps. This review incorporates local and global evidence regarding FinTech adoption by utilizing the Stimulus-Organism-Response (S-O-R) framework, the Unified Theory of Acceptance and Use of Technology (UTAUT), and the Technology Acceptance Model (TAM). While TAM focuses on cognitive aspects like perceived usefulness and ease of use, UTAUT considers social influence and enabling conditions, and S-O-R emphasizes trust, satisfaction, and other experience-related constructs. Cultural, infrastructural, and regulatory factors in emerging economies influence adoption complexity, something all three models fail to address. Based on 66 studies in and outside Bangladesh, this paper identifies and explains the primary factors adoption diffusion gaps: trust and security, social and cultural influences, the customer experience, and the framework of the institution. To address this, the paper develops an integrated multi-level framework to explain FinTech adoption in emerging economies more comprehensively. In order to promote inclusive, sustainable digital financial ecosystems, policymakers, practitioners, and researchers can benefit from the theoretical development and useful advice this framework offers.